PV sector in the European Union countries – Clusters and efficiency - Martins, Florinda (2019)
European Union (EU) due to several challenges that exist nowadays has changed its Energy Policy. In order tofulfill international commitments concerning greenhouse gas emission and to assure safety in supply and stableprices, EU has been a leader in renewable energy. In many EU countries solar energy is a possible and veryviable option. Together with wind energy, photovoltaic energy is the new support core of a low carbon EUeconomy in what concerns electricity production. In this work clusters of countries were generated based on theenergy produced by PV systems and the share of energy from PV systems in the total electricity produced byrenewable sources. This work also analyzed the production of energy from the photovoltaic sector in EU andcompared it with the existing potential for this type of energy. Roughly half of the EU countries are producingenergy within the limits of what is expected, considering the irradiation on optimally inclined plane. Howeversome of them could improve the ratio between energy production and installed power. Considering the leadercountries in energy production from photovoltaic, Czech Republic and Spain are the countries that exceed whatit is expected.